A study of the minimum shift keying modulation scheme - Aldera, Mario Antonio (Department of Electrical Engineering, 2016)
This thesis concerns itself with the study of the Minimum Shift Keying (MSK) modulation scheme. The aspects considered are its operation under non-linear conditions as well as an investigation into the hardware implementation of both coherent and non-coherent MSK modems. The literature on digital data transmission and MSK in particular is surveyed, and a comprehensive theoretical description of MSK is given. In addition, papers on the operation of MSK under non-linear conditions were studied, and their major findings are presented. Due to the lack of theory on the effects of incorrect modulation index on the error performance of MSK, an investigation into this avenue was performed. The design of a correction mechanism for maintaining the modulation index at its correct value is described, and aspects of its implementation are considered. Using the available literature, various modules of which a coherent MSK modem is comprised were developed, and their design is discussed. The design of a non-coherent MSK demodulator is also described.